Aortic Prosthesis-Associated MDR Pseudomonas Infections as a Diagnostic and Therapeutic Challenge - Rita Filipe; Filipa Ceia; Ana Cláudia Carvalho; Margarida Tavares; José Teixeira; António Sarmento (MDPI AG, 2020)
Endovascular prostheses are used to treat life-threatening conditions such as ruptured aortic aneurysms. Prosthetic infection cause significant morbidity and mortality, posing important diagnostic and therapeutic challenges. It is particularly difficult to diagnose and, in the era of multidrug resistance (MDR), these type of infections may become even more difficult to treat. Herein, we reported a case of a secondary prosthetic endovascular infection following repeated bacteremia episodes from a urinary source. This case illustrates an MDR Pseudomonas aeruginosa aortic infection that was difficult to diagnose with no oral antibiotic treatment options.